Structure of human RNA polymerase III - Ewan Phillip Ramsay (Nature Portfolio, 2020)
The eukaryotic RNA Polymerase III transcribes tRNAs, some ribosomal and spliceosomal RNAs. Here, the authors resolve a cryo-EM structure of human RNA Polymerase III in its apo form and complemented it with crystal structures and SAXS analysis of RPC5, revealing insights into the molecular mechanisms of Pol III transcription.